Implementasi aplikasi manajemen pengelolaan profil guru untuk peningkatan kompetensi guru - Yulhendri Yulhendri; Ratnawati Susanto (Lentera Negeri, 2025)
The Community Service Program (PkM) at SDN Wijaya Kusuma 07 was designed as a strategic effort to advance teacher professionalism through the implementation of a web-based digital application. Central to the initiative was the development of a career management system that enables educators to map professional trajectories and engage in ongoing competency assessment. Recognizing the role of teachers as pivotal agents in education, the program emphasized technological support for reflection, planning, and growth. Activities were structured across five phases: baseline competency mapping, stakeholder engagement, digital literacy workshops, application integration, and follow-up evaluation. A participatory framework encouraged collaboration among model teachers, school leaders, and educational stakeholders. The intervention demonstrated measurable gains in pedagogical leadership, career planning capabilities, and digital fluency. Teachers expressed increased autonomy and clarity in planning their professional development. Positive feedback on application usability highlights its effectiveness. The program shows strong potential for broader adoption and contributes to strengthening national efforts toward sustainable educational transformation.